INDIKATOR FAKTOR MANUSIA TERHADAP KECELAKAAN SEPEDA MOTOR - Suraji, Aji; Cakrawala, Muhammad; Tjahjono, Ngudi; B. Effendy, Syahriar (Jurnal Transportasi, 2010)
With regard to the problem of motorcycle accidents in Indonesia, the human factor is unique and complex factors. In this study, an analysis of the contribution of the indicators of human factor in a motorcycle accident was conducted. The results show that lack of discipline committed by riders and high vehicle speeds contribute to and affect motorcycle accident occurrence significantly. Although not too dominant, the rider emotion, lack of concentration when driving, and lack of maturity also have a significant influence on thespeed of motorcycles.Keywords: motorcycle accidents, human factors, lack of discipline, motorcycle speed